A new way of analyzing occlusion 3 dimensionally - Hayasaki, Haruaki; Martins, Renato Parsekian; Gandini Júnior, Luiz Gonzaga [UNESP]; Saitoh, Issei; Nonaka, Kazuaki (Elsevier, 2005)
This article introduces a new method for 3-dimensional dental cast analysis, by using a mechanical 3-dimensional digitizer, MicroScribe 3DX (Immersion, San Jose, Calif), and TIGARO software (not yet released, but available from the author at hayasaki@dent.kyushu-u.ac.jp). By digitizing points on the model, multiple measurements can be made, including tooth dimensions; arch length, width, and perimeter; curve of Spee; overjet and overbite; and anteroposterior discrepancy. The bias of the system can be evaluated by comparing the distance between 2 points as determined by the new system and as measured with digital calipers. Fifteen pairs of models were measured digitally and manually, and the bias was evaluated by comparing the variances of both methods and checking for the type of error obtained by each method. No systematic errors were found. The results showed that the method is accurate, and it can be applied to both clinical practice and research. Copyright © 2005 by the American Association of Orthodontists.
Keywords: cephalometry; computer program; dental care; epidemiology; histology; human; image processing; methodology; odontometry; reproducibility; three dimensional imaging; tooth; tooth arch; tooth occlusion; tooth radiography; Bias (Epidemiology); Cephalometry; Dental Arch; Dental Models; Dental Occlusion; Humans; Image Processing, Computer-Assisted; Imaging, Three-Dimensional; Jaw Relation Record; Odontometry; Reproducibility of Results; Software; Tooth